Enhanced extrinsic dielectric response of TiO2 modified CaCu3Ti4O12 ceramics. Issue 10 (December 2015) - Ouyang, Xin; Habib, Mustafa; Cao, Peng; Wei, Shanghai; Huang, Zhaohui; Zhang, Weijun; Gao, Wei
Abstract: TiO2 modified CaCu3 Ti4 O12 (CCTO) has been synthesized via a facile sol–gel precipitation process followed by solid state sintering. The influence of the precipitated TiO2 crystallites on the microstructure, phase composition, and dielectric properties of CCTO has been investigated. The morphology and chemistry of grain boundaries in CCTO ceramics can be significantly tailored by the initial TiO2 crystallites, which results in enhanced barrier layer capacitor structures. The formation mechanism of barrier layers based on the instability of Cu ions has been discussed. A new bimodal brick layer mechanism has been proposed to explain the effect of TiO2 modification. The optimized TiO2 modified CCTO sample exhibits stable dielectric permittivity which is twice as high as the unmodified one, and shows relatively low dielectric loss over the frequency range from 10 2 to 10 5  Hz. Such enhancement is deemed to arise from the modified and bimodal internal barrier layer capacitor effect.